Design of a web-based car rental service portal information system for 123 Lampung Utara - Sari, Devika; Jihad, M. Abu (Jurnal Mandiri IT, 2025)
This study aimed to design and implement a web-based car rental service information system for 123 Lampung Utara. The system was developed using the CodeIgniter framework with PHP as the programming language and MySQL as the database. The main features included vehicle category and data management, user registration and authentication, rental transactions, order status tracking, and transaction reporting in PDF format. The system was designed to enhance operational efficiency and customer satisfaction through the digitalization of the rental process. The development followed the Waterfall methodology and the Model-View-Controller (MVC) architecture. Black Box testing results showed that all system functions operated correctly according to predefined scenarios, and no critical bugs were found. Therefore, the system was deemed feasible for operational implementation and ready for further development through integration with a payment gateway and automated notification services.